Webinar highlights: transforming pharmacy education transforming pharmacy education through experiential learning - Ramli, Nor Amlizan; Karuppannan, Mahmathi (Faculty of Pharmacy, 2025)
Pharmacy educators and students from the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) and worldwide, were privileged to hear from Professor Dr. Matthew Boyd in a thought-provoking webinar exploring the future of experiential learning in pharmacy education.